UNIT 17.13 Diagnosing Lysosomal Storage Disorders: Fabry Disease. (April 2013) - Bodamer, Olaf A.; Johnson, Britt; Dajnoki, Angela
Abstract: Fabry disease (FD) is an X‐linked lysosomal storage disorder due to deficiency of alpha galactosidase A (GLA). Progressive, intralysosomal accumulation of neutral glycosphingolipids in endothelial cells and podocytes leads to multi‐organ involvement in affected males and to a lesser extent in affected females. Diagnosis of FD is based on GLA analysis in leukocytes or dried blood spots (DBS) in FD males while GLA activities may be within the normal range in FD females. The advent of fluorometric and mass spectrometry methods for enzyme analysis in DBS has simplified the diagnostic approach for FD males, facilitating high‐throughput screening of at risk populations and newborn infants. However, the diagnostic mainstay for FD females remains molecular analysis of the GLA gene. The following unit will provide the detailed analytical protocol for measurement of GLA activity in DBS using tandem mass spectrometry. Curr. Protoc. Hum. Genet. 77:17.13.1‐17.13.7. © 2013 by John Wiley & Sons, Inc.